Literasi Investasi Dasar: dalam Kehidupan Sehari-Hari - Dimas Arya Putra Thampan; Muhamad Ikhsan Romadan; Hana Shaila Manurung; Nur Siti Alfiah; Irenne Putren (Abdimisi, 2025)
The low level of investment literacy among high school students is one of the main causes of the lack of awareness about the importance of early financial management. Many students at SMA Negeri 11 Kota Tangerang Selatan do not yet understand the difference between saving and investing and tend to perceive investment as complex and high-risk. The main issue identified is the limited understanding of basic investment concepts and the lack of guidance on how to manage money productively among the students. This activity aims to improve students’ understanding of investment concepts, their benefits in daily life, and how to start small investments using official instruments regulated by the Financial Services Authority (OJK). The program was implemented through interactive presentations and discussions using simple and student-friendly materials adapted for high school participants. The activity resulted in increased knowledge and awareness among participants about the importance of early investment, the ability to differentiate between investment instruments, and greater awareness of managing pocket money wisely. This activity is expected to foster financial literacy among students and encourage the growth of a financially literate young generation, particularly at SMA Negeri 11 Kota Tangerang Selatan.   Keywords: investment literacy, financial education, basic investment